Students as Contributors: : Reflections on School Education Curriculum Construction Experiences - Paleeri, Sankaranarayanan; MV, Mohammed Shiyas (Voices of Teachers and Teacher Educators, 2024)
The grassroots-level approach to curriculum construction is innovative, emphasizing the acceptance of valuable insights, comments and suggestions from teachers to draft school education curricula. Building on this approach, the Indian state of Kerala has started involving students in curriculum creation processes. This article examines students’ participation in Kerala state school curriculum development procedures. Reflections on curriculum construction experiences and students as contributors to curriculum creation were analyzed in this longitudinal study conducted from 2013 to 2023. Instructors’ field notes and Focus Group Discussion (FGD) reports were utilized to organize the material. Portfolio analysis was also employed to examine the data. Students’ contributions in the curriculum development processes are explained with a comparative analysis from a global viewpoint. The study highlights the potential of students to creatively contribute towards constructing their school education curriculum.